When Silence Speaks: Constraint and Resistance in Nawal El Saadawi’s Woman at Point Zero and Fatou Diome’s Les Veilleurs de Sangomar - Aduh Mary Eleojo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2026)
In El Saadawi’s Woman at Point Zero an Diome’s Les Veilleurs de Sangomar, silence is not emptiness but eloquence; a language of survival born in the shadows of patriarchal, political, and linguistic confinement. Drawing on feminist postcolonial theory and Foucault’s concept of discourse, this study examines how both writers construct silence as a site of resistance and agency. Using a qualitative textual analysis, the paper investigates how the protagonists’ constrained voices expose deeper systems of domination that dictate who may speak and who must remain unheard. Silence, in these narratives, transcends its traditional perception as absence; it becomes a charged form of testimony, memory, and defiance. Through strategies such as code-switching, fragmented narration, and the reactivation of oral traditions, El Saadawi and Diome transform linguistic confinement into creative rebellion. Situated within the politics of gender and language, the study argues that both authors expand the boundaries of expression by transforming silence into discourse. Ultimately, the paper contends that these works illuminate the intricate ties between language, power, and identity, where silence becomes not the end of speech, but its most radical form of expression.